Feasibility Design: Case Study of Rooftop PV System for Pharmaceutical Company - Iskandar, Handoko Rusiana; Fuadiyyah, Siti Syamroatul (Faculty of Engineering Universitas Muhammadiyah Jakarta, 2025)
According to 2019 data, solar energy represents the most significant potential for renewable energy (RE), totalling 207.8 GW. This has propelled the use of solar renewable energy across all industrial sectors, emphasizing ecologically sustainable energy derived from photovoltaic (PV) technology. This context has propelled the design and empirical evaluation of a grid tied rooftop PV system for the load of an Air Handling Unit (AHU) at a corporation. This study delineates various PV roof-top design methodologies, encompassing K2 base system simulation, solar energy potential (kWh/m2/day), available area, component generation capacity, and an analysis of the Levelized Cost of Energy (LCOE), Net Present Cost (NPC), and PV contributions to the RE and PLN grid sources utilizing Homer software. The modelling and analytical results produced an average solar energy of 4.81 kW/m²/day. The usable area encompasses 3,140 m², accommodating 1,324 panels capable of producing 52.6 kWp of energy to meet the existing electricity demand of 5,808 kW/day. The total energy produced is 756,389 kWh, with a renewable share of 33.5%. The NPC value is Rp43,680,200,000.00, the LCOE is Rp1,050.30, the reduction value is 5.8%, and the running cost is Rp2,013,450,000. In contrast to the electricity provided by Grid at 2,119,920 kWh/year, the PV contribution is 1,502,835 kWh/year, resulting in a 29% reduction in emissions.